Perceived classroom disruption undermines the positive educational effects of perceived need-supportive teaching in science. (October 2021) - Burns, Emma C.; Martin, Andrew J.; Collie, Rebecca J.; Mainhard, Tim
Abstract: Extensive research has demonstrated the benefits of need-supportive teaching, but minimal research has examined social factors that may constrain these benefits. One factor that students experience contemporaneously to need-supportive teaching is classroom disruption. Perceived classroom disruption is a barrier to quality teaching and learning, especially in science, and may be a negative moderator of perceived need-supportive teaching. Using structural equation modelling ( N  = 14, 530 students), this investigation examines the extent to which perceived need-supportive teaching and perceived classroom disruption uniquely predicted students' science self-efficacy, participation, and achievement; as well as the extent to which perceived classroom disruption moderates the associations between perceived need-supportive teaching and these outcomes. Findings revealed that perceived need-supportive teaching was positively associated with all outcomes. Perceived classroom disruption was negatively associated with self-efficacy and achievement and attenuated the positive association between perceived need-support and achievement. These results provide insight about the boundary conditions of need-supportive teaching. Highlights: Examined perceived need-supportive teaching alongside classroom disruption. Perceived need-supportive teaching positively predicted all outcomes. Perceived classroom disruption negatively predicted achievement and self-efficacy. Classroom disruption attenuated associations between need-support and achievement. Benefits of need-supportive teaching in science are negated by classroom disruption.